Os saberes docentes e a experimentação com calculadora gráfica: nuances de um projeto temático - Teixeira, Franciele Santos [UNESP] (2025)
In this article, we discuss how visualization and experimentation with technology can be addressed in Mathematics classes based on teachers' demands and needs. For this purpose, we consider two research contexts: one of them, the data production from an ongoing doctoral study, where a training course was proposed with Mathematics teachers, leading to the development of an activity by one of the participating teachers in their classroom; and the other one, it was developed within the context of a completed master's research, where data production occurred in an elective course taught collaboratively by the school teacher and the researcher, with one of the discussions focusing on the Python programming language. Both studies are part of the thematic project Teaching and Learning Mathematics with Calculators: Possibilities for Teacher Practice and had their data produced in the second semester of 2022 in the city of São Carlos. The data discussed in this article come from the researchers' field diary, activities assigned by the teacher, written responses from students to a questionnaire, transcripts of classroom dialogues, and files saved on the graphing calculator. Additionally, we highlight that teachers' repertoire of knowledge was crucial for the experimentation with technology, particularly with graphing calculator, to occur in both scenarios. Additionally, we reflect on the importance of the relationship between university and school, as despite of the importance of teachers' knowledge for the configuration of the observed heuristic environments, this relationship was the basis for the evidenced developments to take place.